Numerical Simulation of Cross-Ply R-Pet Laminated Composites Subjected to Quasi-Static Indentation Test - Mohd Ridzuan, Muhammad Aqil Alimin; Azrin Hani Abdul Rashid; Nurul Zakiah Zamri Tan; Asyran Muhammad Azman (Progress in Engineering Application and Technology, 2022)
Polyethylene Terephthalate (PET) is the most popular thermoplastic that is frequently employed as a reinforcement material in laminated composites due to its lightweight and high strength qualities. In this study, a Finite Element Analysis (FEA) was used to carried out the numerical simulation of quasi-static indentation on r-PET/Epoxy laminated composite. The results from simulation were compared with experimental study which obtained from the secondary data. The FE model for laminated composite panel 100mm x 100mm and a 12.7mm diameter hemispherical tip for indenter was designed and developed for testing using ANSYS R2 2021 software. The materials and layer of r-PET mats were defined in the ANSYS Composite PrePost (ACP) as a single-plate with different stacking orientation. Experimental testing and simulation results were compared to analyze the behavior of the laminated composite. The findings evidenced that the simulation results have different trends with the experimental test. The simulation results show to have larger deformation on the composite panel and higher energy absorption in comparison with experimental. However, these differences are not very significant and still logically acceptable. In shorts, both results demonstrated the high potential of r-PET/Epoxy laminated composite as reinforcement material in the engineering application.